Ammonia as Fuel for Low-Carbon Spark-Ignition Engines of Tomorrow's Passenger Cars - Mounaïm-Rousselle, Christine; Brequigny, Pierre (Frontiers in Mechanical Engineering, 2020)
Faced with the problem of reducing greenhouse gas emissions and transitioning toward a greater use of renewable energies, ammonia, as an energy carrier, is increasingly seen as a potential ‘green’ fuel for transportation, in particular marine applications. However, its combustion characteristics (high minimum ignition energy and auto-ignition temperature, low combustion speed in comparison to usual hydrocarbon fuels) are drawbacks that have so far limited its use. Due to the evolution of different pollutant standards for road transportation, Spark-Ignition engines and thus the combustion process itself have been subjected to many changes over the last 20 years (e.g., gasoline direct injection, downsizing). The objective of this article is to discuss the potential of ammonia as a fuel for spark-ignition engines thanks to the studies carried out so far and to point out directions for future work.